Exploring Indonesian EFL Learners’ Perception of English Learning Grammar - Cahya Komara; Fidaniar Tiarsiwi (Journal of English Language Teaching and Linguistics, 2021)
This study presents Indonesia English as Foreign Language (EFL) learners’ perception of English learning grammar in response of ‘stigma’ appeared among learners where grammar is considered as a difficult but crucial sub-skill to master. The goals of this research are specifically to figure out whether and how grammar is seen as its disreputable status as well as to explore their competence or motivation, what obstacles that learners experience while studying it, and which learning models that learners prefer to apply in their grammar learning. To achieve that aims, this study involves 500 respondents from three different levels of education; lower secondary school learners, upper secondary school learners, and university learners across country using online closes-ended and open-ended questionnaires. The data then was analyzed on the corridor of quantitative and qualitative approaches. The result of this study showed that Indonesia EFL learners truly viewed grammar as difficult but essential to learn and master. Learners had also stated that teachers’ factors and English school textbook became dominant obstacle in comprehending grammar. Last, learners were likely to choose variative models of learning, particularly technology in learning grammar.